Failure patterns and clinical indications in early-stage follicular lymphoma: a study from the National Cancer Center in China - Xu, Chang; Yang, Shijie; Liu, Yue; Wu, Yunpeng; Liu, Xin; Zhong, Qiu-Zi; Yang, Yong; Wu, Tao; Chen, Si-Ye; Chen, Bo; Song, Yong-Wen; Fang, Hui; et al. (Frontiers in Pharmacology, 2026)
Background and PurposeThe optimal management of early-stage follicular lymphoma (FL) remains an active research area, particularly in China. This retrospective cohort study examined long-term survival outcomes, recurrence patterns, and potential prognostic factors in patients with early-stage FL.Materials and MethodsWe retrospectively analyzed 107 patients diagnosed with early-stage FL between 2000 and 2020 at the National Cancer Center in China. Treatment modalities included radiotherapy with or without chemoimmunotherapy or chemotherapy, chemoimmunotherapy or chemotherapy, and observation. Overall survival, progression-free survival, and lymphoma-specific survival were assessed using the Kaplan-Meier method and Cox regression models. We evaluated failure patterns, including locoregional and systemic failures, using cumulative incidence analysis with competing risks. Exploratory LASSO regression and machine learning–based approaches were applied to identify potential prognostic factors.ResultsThe median age was 53 years, and the median follow-up was 86 months. In this 20-year real-world cohort from the National Cancer Center of China (n = 107), long-term outcomes were favorable, with 5- and 10-year rates of 88.7% and 68.8% for OS, 93.3% and 89.9% for LSS, and 76.0% and 57.2% for PFS. No statistically significant differences in survival or cumulative failure were observed across initial management strategies, including radiotherapy with or without systemic therapy, systemic therapy alone, and observation. Recurrence occurred in 21 patients (19.6%), predominantly locoregional (14 locoregional only vs. 6 systemic only; 1 both). The 5- and 10-year cumulative incidences were 16.3% and 19.5% for overall failure, 14.5% and 16.2% for locoregional failure, and 3.1% and 4.8% for systemic failure. POD24 occurred in 6.5% of patients and was associated with inferior OS, although event numbers were limited. Low neutrophil-to-lymphocyte ratio (NLR <1.8) was associated with poorer survival in exploratory analyses.ConclusionPatients with early-stage FL in this 20-year real-world Chinese cohort demonstrated an overall favorable long-term prognosis across diverse initial management strategies. No treatment modality showed a clear survival advantage in this limited-size cohort, while relapse was uncommon and more frequently locoregional than systemic. POD24 identified a small subset of patients with inferior survival, highlighting the need for individualized, risk-adapted management and long-term follow-up.